“ANTESEDEN BELANJA DAERAH DAN KONSEKUENSINYA TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN/KOTA PROVINSI JAWA TENGAH 2014-2016” - Predo Benny Irawan, 14.05.52.0099; Widiatmoko, Jacobus (Students' Journal of Accounting and Banking, 2018)
This study is examines and analyze the effect of original local government revenue, general allocation funds, and special allocation funds of the regional expenditure, and the effect of regional expenditure of the economic growth. The population of this research are district/city central java province which consists of 35 district/city. The study uses secondar data such as realization report 2014-2016 budget. Relations and or influence between variables and is described by using multiple regression analysis. The result showed that the original local government revenue a significant positive effect of the regional expenditure. General allocation funds a significant positive effect of the regional expenditure. Special allocation funds a significant positive effect of the regional expenditure. Regional expenditure a significant positive effect of the economic growth. Keywords: Economic Growth, Regional Expenditure, Original Local Government Revenue, General Allocation Funds, and Special Allocation Funds.